De tre makreller. Om dødelighed og dødsritualer til søs i 1800-tallet - Vognsen, Frederik Lynge (Historisk Tidsskrift, 2025)
The Three Mackerels: Mortality and Funeral Rituals at Sea in the 19th Century Life at sea has always been risky. Nevertheless, many sought the sea, motivated by better pay, career opportunities and a sense of adventure. However, research has rarely paid much attention to the risks of life at sea. This article seeks to correct that by focusing on these risks; it shows that the death rate for adults was significantly higher at sea than on land. The article also points to the tendency that the youngest, most inexperienced sailors were most at risk, although even captains were not assured of their safety. This meant that death was a natural part of everyday life at sea. Therefore, rituals and practices had to be in place to deal with it. The article takes a practice-oriented approach in order to establish a less anecdotal and more source-critical basis for further discussion. Despite this ambition, the article’s sources are fundamentally casuistic in nature, although they are not exactly detailed in their descriptions of death, grief management and rituals at sea. Of these, the dead men’s auction stands out as an important practice, containing ritualistic functions. The auction was part of the formal funeral ritual at sea and imitated burial practices on land. Like all burial rituals it aimed at processing difficult emotions, however, it was also inherently practical: the deceased’s belongings were sold, effectively “removing” the deceased from the ship. What is striking about the sources is the total absence of pronounced religious, superstitious or para-religious rituals that one reads about in many other places. There could be many explanations for this, and it requires further investigation. However, we should take care not to exaggerate the role of superstition in the sailors’ worldview and death cult. If we look at the immediate first-hand sources, such as diaries, which have not been affected by post-rationalisation, the sailors appear to have been governed by manageable rituals that enabled a form of grief processing and were closely linked to actions that could be carried out under most circumstances.